2014
DOI: 10.1088/2040-8978/16/12/125405
|View full text |Cite
|
Sign up to set email alerts
|

Generalized formulation of an encryption system based on a joint transform correlator and fractional Fourier transform

Abstract: Abstract. We propose a generalization of the encryption system based on double random phase encoding (DRPE) and a joint transform correlator (JTC), from the Fourier domain to the fractional Fourier domain (FrFD) by using the fractional Fourier operators, such as the fractional Fourier transform (FrFT), fractional traslation, fractional convolution and fractional correlation. Image encryption systems based on a JTC architecture in the FrFD usually produce low quality decrypted images. In this work, we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
1
48
0
1
Order By: Relevance
“…The DRPE implemented with a JTC architecture has been extended from the Fourier domain to the Fresnel domain [14], the fractional Fourier domain [15][16] and the Gyrator domain [17][18][19]. In the nonlinear approaches [14,16,19], the nonlinear operations introduced in the JTC have become essential to correctly decrypt the input signal with satisfactory quality.…”
Section: Extended Nonlinear Joint Transform Processormentioning
confidence: 99%
See 2 more Smart Citations
“…The DRPE implemented with a JTC architecture has been extended from the Fourier domain to the Fresnel domain [14], the fractional Fourier domain [15][16] and the Gyrator domain [17][18][19]. In the nonlinear approaches [14,16,19], the nonlinear operations introduced in the JTC have become essential to correctly decrypt the input signal with satisfactory quality.…”
Section: Extended Nonlinear Joint Transform Processormentioning
confidence: 99%
“…In the nonlinear approaches [14,16,19], the nonlinear operations introduced in the JTC have become essential to correctly decrypt the input signal with satisfactory quality. Moreover, the extension to other domains has increased the security of the overall encryption-decryption system by introducing new parameters that must be adjusted prior to obtaining the hidden information.…”
Section: Extended Nonlinear Joint Transform Processormentioning
confidence: 99%
See 1 more Smart Citation
“…We use the GT to improve the security of the original DRPE by adding a new key for the encryption system (the rotation angle of the GT). It has been demonstrated that the nonlinearities introduced in the initial DRPE leading to an improvement in security [3,5,11,14]. The generation of the RPMs by using a chaotic map allows to obtain the chaotic RPMs or CRPMs with a higher security.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main drawbacks of the image encryption systems based on the initial DRPE is that the security of the system is vulnerable to attacks, this weakness is due to the linear property of the DRPE scheme [1][2][3]. The DRPE has been further extended from the Fourier domain to the Fresnel domain [4][5][6], the fractional Fourier domain [7][8][9][10][11][12], the Gyrator domain (GD) [13][14][15][16] and other domains [17][18][19][20], with the purpose of adding more keys and increasing the security of the DRPE system.The Gyrator transform (GT) is a mathematical tool for analysis and processing of twodimensional signals [21]. The GT has been used in optics [22], signal processing [13] and image encryption [13][14][15][16].…”
mentioning
confidence: 99%